PENGAPLIKASIAN MEDIA STREAMING PADA M-LEARNING DENGAN MENGGUNAKAN SELULAR CDMA - Santoso, Gatot (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2005)
Telecommunications technology and internet technology represent a most tech-nology liked in the world. In this technological growth enable new breakthrough in learn-ing by mobile use IT peripheral grasp or referred as mobile learning ( m-learning). M-Le-arning have some excess among others ability learn